ANALISIS TINDAK TUTUR PERLOKUSI PADA FILM SEJUTA SAYANG UNTUKNYA KARYA HERWIN NOVIANTO SEBAGAI PEMANFAATAN BAHAN AJAR TEKS ULASAN DI SMA - Rifa Nurjanah (STKIP Subang, 2023)
Humans use language to give and receive information through various types of media, including audio and visual media. In speech events, sentences show the intent and purpose of communicating. The words spoken by a speaker can indicate the intent of the speaker or speakers so that other people can understand them more easily. In every communication process, speech events and speech acts occur. Speech acts are strongly influenced by the context or speech situation. This is due to the fact that the speaker and the interlocutor are talking about the same topic, at a certain time, place and situation, so that both of them can understand well the intended meaning of the conversation. In a situation where someone is speaking, their language skills greatly influence what they are saying. One of the main problems that often occur in communication is the difficulty of expressing the information to be communicated. The term